Peran Asuransi Syariah dalam Pertumbuhan Perokonomian di Indonesia - Fairuzzen, Mohamad Revaldy; Reihan, Akmal; Kenjiroh, Benny; Saputra, Fernando; Dr Mahipal, S.H, M.H. (Interdisciplinary Explorations in Research Journal, 2024)
Abstract Economic development in Indonesia has become the main focus in efforts to achieve sustainable and inclusive economic growth. In this context, the role of sharia insurance has become increasingly important as a financial instrument that supports economic stability and protects financial risks. This study aims to analyze the contribution of sharia insurance to economic development in Indonesia.This research uses descriptive and quantitative analysis methods to evaluate the impact of sharia insurance on the Indonesian economic sector. The results of the analysis show that sharia insurance has played a significant role in reducing financial risks for individuals, companies and the government. Through a risk sharing mechanism based on sharia principles, sharia insurance helps reduce uncertainty and increase public trust in the financial system.Apart from that, sharia insurance has also played an important role in mobilizing investment funds for key economic sectors, such as infrastructure, agriculture and creative industries. By providing products that comply with sharia principles, sharia insurance encourages financial inclusion and sustainable growth of economic sectors.Nevertheless, challenges still exist in optimizing the role of sharia insurance in Indonesia's economic development. Strategic steps are needed, including improving regulations, public education and product innovation, to strengthen sharia insurance's position as a driver of sustainable and inclusive economic growth in Indonesia. Keywords: Sharia Insurance, Economic Development, Indonesia, Sharia Finance, Financial Inclusion. Abstrak Perkembangan ekonomi di Indonesia telah menjadi fokus utama dalam upaya mencapai pertumbuhan ekonomi yang berkelanjutan dan inklusif. Dalam konteks ini, peran asuransi syariah telah menjadi semakin penting sebagai instrumen keuangan yang mendukung stabilitas ekonomi dan melindungi risiko finansial. Studi ini bertujuan untuk menganalisis kontribusi asuransi syariah terhadap perkembangan ekonomi di Indonesia.Penelitian ini menggunakan metode analisis deskriptif dan kuantitatif untuk mengevaluasi dampak asuransi syariah terhadap sektor ekonomi Indonesia. Hasil analisis menunjukkan bahwa asuransi syariah telah berperan secara signifikan dalam mengurangi risiko finansial bagi individu, perusahaan, dan pemerintah. Melalui mekanisme pembagian risiko berdasarkan prinsip syariah, asuransi syariah membantu mengurangi ketidakpastian dan meningkatkan kepercayaan masyarakat terhadap sistem keuangan.Selain itu, asuransi syariah juga telah memainkan peran penting dalam memobilisasi dana investasi untuk sektor-sektor ekonomi kunci, seperti infrastruktur, pertanian, dan industri kreatif. Dengan menyediakan produk-produk yang sesuai dengan prinsip syariah, asuransi syariah mendorong inklusi keuangan dan pertumbuhan sektor-sektor ekonomi yang berkelanjutan.Meskipun demikian, tantangan masih ada dalam mengoptimalkan peran asuransi syariah dalam perkembangan ekonomi Indonesia. Diperlukan langkah-langkah strategis, termasuk peningkatan regulasi, edukasi masyarakat, dan inovasi produk, untuk memperkuat posisi asuransi syariah sebagai pendorong pertumbuhan ekonomi yang berkelanjutan dan inklusif di Indonesia. Kata kunci: Asuransi Syariah, Perkembangan Ekonomi, Indonesia, Keuangan Syariah, Inklusi Keuangan.